Developing water resources decision support system to strengthen landscape resilience planning and investment in West and Central Africa: a scoping and needs assessment report - Amponsah, Andoh Kwaku; Atampugre, Gerald; Tilahun, Seifu A.; Oke, Adebayo (International Water Management Institute (IWMI). CGIAR Initiative on West and Central African Food Systems Transformation, 2023)
The International Water Management Institute (IWMI) conducted a virtual scoping and need assessment workshop to develop a water resources decision support system (DSS) to strengthen landscape resilience planning and investment in West and Central Africa. The workshop, which took place on May 8, 2023, involved 51 participants from the public sector, private companies, research, and civil society organizations, as well as academia of six countries: Ghana, Nigeria, Cote d’Ivoire, Burundi, DRC, and Rwanda. The objective was to explore the current data gaps, information, and knowledge products in water DSS, where IWMI could provide support on appropriate science-based decision-support systems for water resources management, with a particular emphasis on strengthening landscape resilience planning and investment in the respective countries within the TAFS-WCA initiative. Most participants from six countries expressed interest in AWARE, a flood forecasting tool of IWMI, which facilitates coordination across sectors to trigger actions ahead of extreme climate events. Stakeholder mapping, end-user participation, comprehensive needs assessments, expert maintenance, and knowledge-sharing forums were identified as crucial for successful DSS implementation as part of reflection in the meeting.